THE CR-CR2O3 OXYGEN BUFFER AND THE FREE ENERGY OF FORMATION OF CR2O3 FROM HIGH-TEMPERATURE ELECTROCHEMICAL MEASUREMENTS - Holzheid A.; O'Neill H.S.C. (My University, 1995)
The free energy of formation of Cr2O3, defined by the reaction2 Cr + 32 O2 = Cr2O3, has been measured electrochemically using a yttria-doped thoria (YDT) solid electrolyte, in the temperature range from 900 to 1400 K. Fe + ''FeO'' was used as the reference electrode.The results have been combined with high temperature heat capacity data from the literature, to give, in J.mol-1μO2(+/- 170) = -758,585 + 349.718T - 25.5216T 1n T + 0.00935T2 (600 K < T < 1800 K) .Our results are not in good agreement with the calorimetric data and imply that the currently accepted calorimetric value for the entropy of Cr2O3 at 298.15 K may be too low by 4.6 J/K . mol.